TVA-based assessment of visual attentional functions in developmental dyslexia - Bogon, Johanna; Finke, Kathrin; Stenneken, Prisca (Frontiers in Psychology, 2014)
There is an ongoing debate whether an impairment of visual attentional functions constitutes an additional or even an isolated deficit of developmental dyslexia (DD). Especially performance in tasks that require the processing of multiple visual elements in parallel has been reported to be impaired in DD. We review studies that used parameter-based assessment for identifying and quantifying impaired aspect(s) of visual attention that underlie this multi-element-processing deficit in DD. These studies used the mathematical framework provided by the ‘theory of visual attention’ (TVA; Bundesen, 1990) to derive quantitative measures of general attentional resources and attentional weighting aspects on the basis of behavioral performance in whole- and partial-report tasks. Based on parameter estimates in children and adults with DD, the reviewed studies support a slowed perceptual processing speed as an underlying primary deficit in DD. Moreover, a reduction in visual short term memory storage capacity seems to present a modulating component, contributing to difficulties in written language processing. Furthermore, comparing the spatial distributions of attentional weights in children and adults suggest that having limited reading and writing skills might impair the development of a slight leftward bias, that is typical for unimpaired adult readers.